The Hermeneutics and Listener Reception of the Song “Ma Syamamtul Warda” and the Lesson Plan - Barnabila, Muhammad Kesit; Mu'ammar, Naufal; Zakaria, Muhammad Thoriq Zizad; Yusuf, Kamal (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
Arabic songs that go viral on Indonesian social media are often enjoyed aesthetically without a deep understanding of the lyrics' meaning. One of them is a song entitled "Ma Syamamtul Warda," discovered by Toha Fasyni. The purpose of this study is to: 1) explain the meaning of the song "Ma Syamamtul Warda" hermeneutically; 2) find out the listener's reception of the song "Ma Syamamtul Warda"; 3) the plan lesson plan that involves innovative strategies through special modules. The method used in this study is descriptive-qualitative by combining literature reviews and field studies. Data were collected using observation guidelines and in-depth interview guidelines with several students. The data analysis technique employs Stuart Hall's hermeneutic encoding/decoding theory, which categorizes a person's understanding into three categories: hegemony-dominance, negotiation, and opposition. The results of the analysis show that: 1) the lyrics of the song "Ma Syamamtul Warda" have symbolic, Sufi, spiritual, and cosmic elements that are shown through each verse; 2) The majority of listeners' reception of the song "Ma Syamamtul Warda" shows the category of hegemonic-dominant decoding and there is one lyric that is interpreted by the informant with the category of negotiation decoding. Meanwhile, the category of opposition decoding, which indicates that listeners can interpret the song effectively, was not identified; 3) the lesson plan in class X of high school involves 10 core activities that incorporate innovative strategies through special modules.